Sosialisasi Produk Hasil Olahan Ternak sebagai Upaya Pencegahan Stunting Bayi dan Anak di Pontianak Utara - Dela Heraini; Ira Erdiandini (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
This service is carried out to provide information about processed livestock products as an effort to prevent stunting in infants and children. The service was held on February 28, 2021 with female participants who were members of the Family Welfare Development (PKK) in the Siantan Hilir sub-district, North Pontianak. The method used in this service is socialization in the form of delivering information on processed livestock products as an effort to prevent stunting in infants and children. There are three stages carried out namely the stages of preparation, implementation, and evaluation. The outreach was carried out as targeted. All participants gained additional knowledge and understanding related to stunting and its prevention through consumption of processed livestock products which are not difficult to find. The low understanding before this socialization was carried out then the participants became more aware of the importance of preventing stunting starting from babies in the womb to post-delivery. There is an opportunity to change the behavior of participants in neglecting the food and snacks consumed by their children. Therefore, it is necessary to do the same thing at various levels of society as participants in a wider socialization.